Fostering students’ creative thinking when teaching poetry writing in a foreign language - E. A. Gradaleva; M. O. Polukhina (Вестник Самарского университета: История, педагогика, филология, 2024)
The article is dedicated to studying and developing strategies for fostering creative thinking among students through the teachingof poetry writing in a foreign language. In professional activities, creative thinking is evident when one must act in situations of uncertainty, lack of standard problem-solving methods, and rapidly changing conditions. A set of exercises for preparing students to create poetic texts has been proposed and tested. Both standard methods and new ones, based on the theoretical principles of D. Hanauer, are applied, ensuring a high-quality preparatory stage that motivates students to self-discovery and self-expression. The experiment showed that 100 % of the participants not only demonstrated their ability to independently complete the final task using literary techniques but also displayed deep involvement in the process of writing poetry. They were able to merge the content of the novel with their own memories and emotions, creating unique and emotionally rich poetic works. The obtained results have practical applications in the field of developing students’ creative thinking when studying a foreign language.